A circular solution to enhance the food-water nexus by nanocellulose technologies for ammonium recovery and reuse - Ken I Johnson; Grenalynn Ilacas; Rasel Das; Hao-Yen Chang; Priyanka R Sharma; Christian O Dimkpa; Benjamin S Hsiao (Sustainability Science and Technology)
In this study, a circular solution to enhance the food and water nexus by using a zero-waste process to produce carboxylated nanocellulose adsorbents from a model lignocellulose feedstock (jute) for ammonium (NH _4 ^+ ) nutrient recovery and reuse was demonstrated. The study represents a new pathway to close the nitrogen loop that will be suitable for some agricultural practices. In specific, anionic nanocellulose containing COO ^− groups, produced by the nitro-oxidization process, are efficient for removing NH _4 ^+ from contaminated water, where the spent adsorbent can be repurposed as an effective plant fertilizer. The nitro-oxidized cellulose nanofiber (NO-CNF) scaffold prepared from raw jute exhibited a maximum adsorption capacity of 22.7 mg g ^−1 for NH _4 ^+ removal, which is significantly higher than any natural sorptive materials reported thus far, including biochar and activated carbons. The effect of pH (from 2 to 10) on the ammonium adsorption efficiency and the corresponding zeta potential of NO-CNF was investigated, where the optimal adsorption capacity was near neutral pH conditions. The zeta potential of ammonium-loaded NO-CNF was found to covert from a negative value (−50 mV) to a positive value (100 mV) with the increasing ammonium content at a critical NH _4 ^+ :COO ^− molar ratio around 0.85). The NH _4 ^+ -loaded NO-CNF was repurposed as a fertilizer for soybean growth with efficacy similar to a typical urea fertilizer. This study illustrates an exemplary advance in the development of zero-waste process to upcycle natural waste feedstocks into valued products that can simultaneously reduce nitrogen pollution problems and close the nitrogen loop for food production.